Financial accounting and reporting : standards and applications : PFRSs and PASs-based : volume 2 - Cabrera, Ma. Elenita Balatbat; Ocampo, Reynaldo Royo (Recto, Manila : GIC Enterprises & Co. Inc., 2014)
This textbook is the second part of a three volume series designed to address the needs of accounting students, faculty and practitioners with the adoption of the International Accounting Standards in the Philippines.
IV. Financial and non-financial liabilities: accounting and reporting -- V. Owners' equity: Accounting and reporting -- VI. Other special topics -- References.
Includes bibliographical references.
Keywords: ACCOUNTING -- STUDY AND TEACHING